Politik Pendidikan Dan Kebijakan Pemerintah Terhadap Pendidikan Islam Di Indonesia - S, Rahmad; Zulmuqim; Muhammad, Zalnur (STAIN Bengkalis, 2023)
Education is an effort to develop the human potentials of students, both their physical potential, their creative potential, taste and intention, so that this potential becomes real and can function in their life journey. The politics of education in question is manifested in the government's strategic policies in the field of education. The expected education politics is, of course, educational politics that side with the small or poor people. This study uses library research methods (Library Research). Which data previously collected was based on library data and did not use empirical tests. The politics and power of a country holds the key to the success of education. In the context of democratization and decentralization development in Indonesia, the role of executive and legislative politics to advance education is enormous. The realm of politics and power must be able to realize an education system that educates and enlightens the civilization of this nation. A nation with bad educational politics will have poor educational performance. On the other hand, a country with good educational politics will also have good educational performance. Since independence until the reform era, the political journey of national education has undergone three changes, namely in the Old Order era, in 1954, in the New Order era, and currently in the reform era. Pendidikan adalah upaya mengembangkan potensi-potensi manusiawi peserta didik baik potensi fisik potensi cipta, rasa, maupun karsanya, agar potensi itu menjadi nyata dan dapat berfungsi dalam perjalanan hidupnya. Politik pendidikan yang dimaksud termanifestasikan dalam kebijakan- kebijakan strategis pemerintah dalam bidang pendidikan. Politik pendidikan yang diharapkan tentunya politik pendidikan yang berpihak pada rakyat kecil atau miskin. Penelitian ini menggunakan metode penelitian kepustakaan (Library Research). Yang mana data-data yang dikumpulkan sebelumnya berdasarkan data kepustakaan dan tidak menggunakan uji empirik. Politik dan kekuasaan suatu negara memegang kunci keberhasilan pendidikan.Dalam konteks pembangunan demokratisasi dan desentralisasi di Indonesia, peran politik eksekutif dan legislatif untuk memajukan pendidikan begitu besar. Ranah politik dan kekuasaan harus mampu mewujudkan sistem pendidikan yang mencerdaskan dan mencerahkan peradaban bangsa ini.Bangsa yang politik pendidikannya buruk, maka kinerja pendidikannya pun pasti buruk. Sebaliknya, negara yang politik pendidikannya bagus, kinerja pendidikannya pun juga akan bagus. Semenjak kemerdekaan sampai dengan era reformasi perjalanan politik pendidikan nasional telah mengalami tiga kali perubahan, yaitu di era orde lama, pada tahun 1954, di era orde baru, dan saat ini di era reformasi.